STRESS COPING STRATEGIES OF HEALTH STUDENTS AT TAY NGUYEN UNIVERSITY - Thi Thao, Le; Thi Giang Thanh, Chu (Journal of Health and Aging, 2025)
To assess the level of stress and describe the coping strategies of health students at Tay Nguyen University. A cross-sectional descriptive study was conducted on 424 students of General Medicine, Bachelor of Nursing, and Bachelor of Medical Laboratory Technology at Tay Nguyen University. The stress rate among health students at Tay Nguyen University is 84.0%. Of these, mild stress accounts for 34.9%, moderate stress for 40.1%, and severe stress for 9.0%. Stressed students often use the coping strategy of "cognitive restructuring" with an average score of 2.22 ± 0.63, and "problem-solving" with an average score of 2.37 ± 0.64. The rate of stressed students is relatively high. The majority of students use active coping strategies. However, inappropriate strategies still exist, so it is necessary to provide timely support interventions to improve students' physical and mental health.
Keywords: stress; coping; students